TOF-SIMS Analysis of Red Color Inks of Writing and Printing Tools on Questioned Documents - Lee, Jihye; Nam, Yun Sik; Min, Jisook; Lee, Kang-Bong; Lee, Yeonhee (WILEY-BLACKWELL, 2016)
Time-of-flight secondary ion mass spectrometry (TOF-SIMS) is a well-established surface technique that provides both elemental and molecular information from several monolayers of a sample surface while also allowing depth profiling or image mapping to be performed. Static TOF-SIMS with improved performances has expanded the application of TOF-SIMS to the study of a variety of organic, polymeric, biological, archaeological, and forensic materials. In forensic investigation, the use of a minimal sample for the analysis is preferable. Although the TOF-SIMS technique is destructive, the probing beams have microsized diameters so that only small portion of the questioned sample is necessary for the analysis, leaving the rest available for other analyses. In this study, TOF-SIMS and attenuated total reflectance Fourier transform infrared (ATR-FTIR) were applied to the analysis of several different pen inks, red sealing inks, and printed patterns on paper. The overlapping areas of ballpoint pen writing, red seal stamping, and laser printing in a document were investigated to identify the sequence of recording. The sequence relations for various cases were determined from the TOF-SIMS mapping image and the depth profile. TOF-SIMS images were also used to investigate numbers or characters altered with two different red pens. TOF-SIMS was successfully used to determine the sequence of intersecting lines and the forged numbers on the paper.
Keywords: ION MASS-SPECTROMETRY; BALLPOINT PEN INKS; FORENSIC ANALYSIS; PAPER; DISCRIMINATION; CHROMATOGRAPHY; SPECTROSCOPY